POST-ISLAMISM: EMERGENCE AND DEVELOPMENT IN INDONESIA - SITI, M.; ALAMSYAH, ALAMSYAH (Utopía y Praxis Latinoamericana, 2021)
The emergence of Post-Islamism in Indonesia in the 1970s was a manifestation of the rejection of the powers that existed. This study uses a qualitative method with a historical contextualist approach and the theory of power relations from Michel Foucault. The results of this study can provide an overview to readers in particular and developers of knowledge generally related to the term trend of Post-Islamism which has always been a hot conversation in the global world. Islam is very different from Islamism, Islam is not a religion of politics, Islamism uses Islam for political strife and Post-Islamism rejects it.